Characterization of the structure and properties of processed alumina-graphene and alumina-zirconia composites. Issue 1 (1st January 2021) - Duntu, Solomon Hanson; Tetteh, Francis; Ahmad, Iftikhar; Islam, Mohammad; Boakye-Yiadom, Solomon
Abstract: The onset of hybrid alumina-based composites, which combines two or more nano-particles within the alumina matrix has already shown promising improvements in the matrix material. However, variations in mechanical properties including the optimum compositions that give improved properties faced with the development of alumina-based composites require further studies to understand the underlying mechanisms and synergistic effects of the nano-particle additions on the alumina matrix. In the current study, the structure and properties of Al₂O₃-graphene (0.5 wt%) and Al₂O₃–ZrO₂ (4 wt% and 10 wt%) composites fabricated via hot-pressing was studied as a baseline for multiple combinations. Even though the addition of 10 wt%ZrO₂ resulted in a 23% reduction in the grain size of the alumina matrix, the 4 wt%ZrO₂ addition resulted in a 14% increase in grain size as compared to the parent alumina matrix. X-ray diffraction analysis revealed that there was approximately 85% monoclinic ( m -ZrO2 ) vs. 15% tetragonal ( t -ZrO2 ) crystal structures in the A4ZrO₂ sample whilst the A10 ZrO₂ had approximately 93% m -ZrO2 vs. 7% t -ZrO2 . The high-volume fraction of the monoclinic crystal structures in the A10 ZrO₂ accounts for the induced microcracks in the sample since the transition from the ductile-tetragonal to brittle-monoclinic is associated with the exertion of compressive stresses on the alumina matrix by the associated elastic volume expansion of m -ZrO2 . Also, the addition of 0.5 wt%graphene resulted in about 37% reduction in the grain size of the alumina matrix, and approximately 10% increase in hardness as a result of the distribution of graphene along the grain boundaries of the parent alumina matrix, which restricts grain coalescence and growth during processing. Furthermore, an increase up to 115% and 164% were observed in the fracture toughness (KIC ) with the inclusion of 0.5 wt%graphene and 10 wt%ZrO₂ respectively, which was primarily ascribed to the fine-grained microstructures and toughening mechanisms of the intergranular graphene and ZrO₂ particles.